2013
DOI: 10.4028/www.scientific.net/amr.750-752.1007
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Luminescence of Terbium Complexes with 2,3-Pyrazinedicarboxylate by Y(III) Doping

Abstract: Ten kinds of terbium doped inert yttrium complexes with 2,3-pyrazinedicarboxylate (2,3-pzdc2-) have been synthesized. Characterization results indicate that the complexes have the compositions of Tb (pzdc)1.55H2O and TbxYy(pzdc)1.55H2O (x:y=0.10:0.90; 0.20:0.80; 0.30:0.70; 0.40:0.60; 0.60:0.40; 0.70:0.30; 0.80:0.20; 0.90:0.10). IR spectra show that the lanthanide ions coordinate with the carboxylic oxygen atoms and nitrogen atoms of the ligands. Luminescence spectra show that the Y(III) ions can remarkably inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…The PBA-P(MMA-ITA) core-shell elastic particles were used to toughen and modify PA 6, the compatilizer was not added at the process of blending modification, because core shell elastic particles had the function of compatibilization by itself [4] . The PBA-P(MMA-ITA-DGEBA) core-shell latex particles with epoxy groups in shell were used to toughen and modify epoxy resin, the SEM was used to observe impact cross section of specimens, the experiment showed that core-shell latex particles had the obvious toughening effect for epoxy resin and good compatibility with epoxy resin at the same time [5,6] . With the deepening of the research, there are many reports about preparation, performance and application of core-shell latex particles, but the research of core-shell latex particles modified polyurethane elastomer was rare.…”
Section: Introductionmentioning
confidence: 99%
“…The PBA-P(MMA-ITA) core-shell elastic particles were used to toughen and modify PA 6, the compatilizer was not added at the process of blending modification, because core shell elastic particles had the function of compatibilization by itself [4] . The PBA-P(MMA-ITA-DGEBA) core-shell latex particles with epoxy groups in shell were used to toughen and modify epoxy resin, the SEM was used to observe impact cross section of specimens, the experiment showed that core-shell latex particles had the obvious toughening effect for epoxy resin and good compatibility with epoxy resin at the same time [5,6] . With the deepening of the research, there are many reports about preparation, performance and application of core-shell latex particles, but the research of core-shell latex particles modified polyurethane elastomer was rare.…”
Section: Introductionmentioning
confidence: 99%